The Media Market in the Classroom: Simulation and participation as teaching innovation mechanisms in the subject ‘Global Media Structure’ - Cañedo, Azahara (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article presents the teaching approach of the subject ‘Global Media Structure’, part of the curriculum of the Audiovisual Communication Degree at the University of Castilla-La Mancha. From the description and analysis of the teaching experience implemented during the 2021-2022 academic year, based on simulation and student participation in the curricular development, the applied teaching innovations, and the learning outcomes identified are highlighted. These results, grounded on the promotion of teamwork and the students’ analytical-critical competence, indicate that the teaching methodology proposed favours the acquisition of competences and dynamizes the learning process despite the intrinsic difficulty of the subject.